Perancangan Iklan Layanan Masyarakat Bahaya Radiasi Saat Tidur - Ika Novita Sari; Siti Ashlihatul Hasanah; Siti Nur Halimah (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2019)
Smartphone is a technology that is currently a primary need. Existing work will be lighter with the smartphone. In addition to the benefits that can help alleviate human work, smartphones also have a negative impact, namely the dangers of radiation caused. Many of us who put smartphones next to us while sleeping without knowing the dangers of radiation coming from smartphones. This public service advertisement is aimed at teenagers as the most smartphone users. By using effective design methods, you will get the most exact results. Keywords : Mobile, Public Service Advertisement, Planning, Radiation